ナンキョク オゾンホール カイフク ジ ノ ユソウ コンゴウ カテイ - 冨川, 喜弘; トミカワ, ヨシヒロ; 佐藤, 薫; サトウ, カオル; Tomikawa, Yoshihiro; Sato, Kaoru (2010)
P(論文) 第44次日本南極地域観測隊は,南極オゾンホールの形成過程に加え,その消滅過程の時間発展とメカニズムを明らかにすることを目的として,2003年6月～ 2004年1月にかけて南極昭和基地(69.0゜S,39.6゜E)でオゾンゾンデ集中観測を行った.上記オゾンゾンデデータと衛星観測データを用いた解析から,極渦崩壊前からブリューワー・ドブソン循環の下降流と中緯度との大気交換による極渦内のオゾン回復が始まっていることがわかった.また,波数1の準停滞性プラネタリー波の活動により,極渦内のオゾン回復の様相が経度によって大きく異なることがわかった.さらに,オゾンホール内に見られるオゾン増大層の解析から,極渦境界領域起源の空気塊が頻繁にオゾンホール内に流入していたことも明らかとなった. The 44th Japanese Antarctic Research Expedition (JARE-44) performed intensive ozonesonde observations at Syowa Station (69.0゜S, 39.6゜E) from June 2003 through January 2004 to clarify the time evolution and mechanism of the Antarctic ozone hole dissipation as well as its formation. From analysis of the ozonesonde and satellite observational data, it was found that ozone concentration inside the Antarctic ozone hole began to increase due to the Brewer-Dobson circulation and the lateral mixing between inside and outside the polar vortex even before its breakup. In addition, the ozone increase was dependent on longitude because of the zonal wavenumber 1 quasi-stationary planetary waves. It is also reported that the ozone enhanced layers frequently observed inside the Antarctic ozone hole mostly originated from the vortex boundary region. departmental bulletin paper